2018
DOI: 10.33549/physiolres.933591
|View full text |Cite
|
Sign up to set email alerts
|

Akt Substrate of 160 kDa Dephosphorylation Rate Is Reduced in Insulin-Stimulated Rat Skeletal Muscle After Acute Exercise

Abstract: Because greater Akt substrate of 160 kDa (AS160) phosphorylation has been reported in insulin-stimulated skeletal muscles without improved Akt activation several hours post-exercise, we hypothesized that prior exercise would result in attenuated AS160 dephosphorylation in insulin-stimulated rat skeletal muscle. Epitrochlearis muscles were isolated from rats that were sedentary (SED) or exercised 3 h earlier (3 h post-exercise; 3hPEX). Paired muscles were incubated with [3H]-2-deoxyglucose (2-DG) without insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
(27 reference statements)
2
12
0
Order By: Relevance
“…However, when a TBC1D4-Ser711Ala mutant is overexpressed in skeletal muscle by gene electrotransfer, the ability of insulin to enhance phosphorylation of TBC1D4-Thr649 is impaired (14), suggesting that Ser711 phosphorylation increases the potential of upstream kinase Akt to phosphorylate TBC1D4. This seemingly increased effect of Akt on TBC1D4 several hours after prior AMPK activation by AICAR and contraction may be mediated by altered cellular localization of TBC1D4 and/or a decreased ability of phosphatases to dephosphorylate TBC1D4 during submaximal insulin concentrations (24,25). Taken together, our observations may suggest that activation of AMPK in some way primes TBC1D4 for a subsequent insulin stimulus, which leads to enhanced insulin-stimulated glucose uptake.…”
Section: Discussionmentioning
confidence: 65%
“…However, when a TBC1D4-Ser711Ala mutant is overexpressed in skeletal muscle by gene electrotransfer, the ability of insulin to enhance phosphorylation of TBC1D4-Thr649 is impaired (14), suggesting that Ser711 phosphorylation increases the potential of upstream kinase Akt to phosphorylate TBC1D4. This seemingly increased effect of Akt on TBC1D4 several hours after prior AMPK activation by AICAR and contraction may be mediated by altered cellular localization of TBC1D4 and/or a decreased ability of phosphatases to dephosphorylate TBC1D4 during submaximal insulin concentrations (24,25). Taken together, our observations may suggest that activation of AMPK in some way primes TBC1D4 for a subsequent insulin stimulus, which leads to enhanced insulin-stimulated glucose uptake.…”
Section: Discussionmentioning
confidence: 65%
“…Exactly how this may relay to the regulation of insulin action following exercise is still unclear. Rodent studies suggest that the localization of TBC1D4 and protection against dephosphorylation mediated by prior exercise might be of importance (Zheng & Cartee, 2016;Arias et al 2018). In the present study, we showed decreased AMPKγ 3 expression in skeletal muscle in response to 12 weeks of cycling exercise, confirming previous observations (Frøsig et al 2004;Wojtaszewski et al 2005;Mortensen et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence support the idea that enhanced AS160 phosphorylation is linked to improved insulin sensitivity postexercise. Acute exercise can induce elevated Thr642 and/or Ser588 phosphorylation in the rat epitrochlearis muscle (3,10,17,48). Greater AS160 phosphorylation has also been reported in insulin-stimulated human muscle after exercise that improved insulin-stimulated glucose uptake (42).…”
Section: Introductionmentioning
confidence: 95%